2016
DOI: 10.16965/ijar.2016.227
|View full text |Cite
|
Sign up to set email alerts
|

A Computerized Tomographic Study of Morphology and Pneumatization of Crista Galli

Abstract: Introduction:Asymmetrically divided sphenoid sinuses exhibits a variety of variation in the presentation of inter sinus septum. Previous reported range of incidence of single midline inter-sphenoid sinus septum is from 18.2% to 95%. Many studies have reported differing incidences of laterally placed septum, accessory septa, multiple septa, transverse septa and no septum in the sphenoid sinuses. Termination of inter-sphenoid septum either into internal carotid canal or into optic canal had also been shown in ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Last, the demographics of the patients used in the studies varied, as some researchers created groups based on their age while others did not. As some of the studies showed, PCG is often connected to the frontal sinus 3–8 . Since the development of frontal sinuses lasts until puberty, 20 age is an important factor in PCG incidence.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Last, the demographics of the patients used in the studies varied, as some researchers created groups based on their age while others did not. As some of the studies showed, PCG is often connected to the frontal sinus 3–8 . Since the development of frontal sinuses lasts until puberty, 20 age is an important factor in PCG incidence.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have been reported on the incidence of PCG, with stunningly different results ranging from 2.4% to 86%. [2][3][4][5][6][7][8][12][13][14][15][16][17][18][19] All of them, except that by Mladina et al, 16 were radiologic studies that investigated CT scans of symptomatic patients. To our best knowledge, this is the first histopathologic study of the incidence of PCG.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The pneumatization area in the crista galli region of the ethmoid bone is called sinus crista galli (SCG), which is a part of the ethmoid bone embryologically. However, studies have reported that crista galli pneumatization is associated with the frontal sinus (Som et al, 2009;Kamala et al, 2016;Mladina et al, 2017).…”
Section: Introductionmentioning
confidence: 99%